ETIKA KOMUNIKASI: SUATU STUDI KOMPARATIF ANTARA ISLAM DAN BARAT - rahmatul akbar (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2019)
The concept of communication not only examines and discusses what is related to speaking effectively but also discusses how to speak ethics. Ethics is a very important side in life. So it is with ethics in communication. Communication that occurs cannot be separated from ethical elements both consciously and unconsciously. The concept of ethics in communication sometimes collides between understanding western communication and Islamic communication. In general, there are similarities in the concept of communication ethics. However, there are differences that sometimes unwittingly become problems arising from communication. By using literature review, this paper wants to see the comparative aspect between Islam and the West on ethics in communication.